The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12974-018-1094-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial damage and “plugging” of transport selectively in myelinated, small-diameter axons are major early events in peripheral neuroinflammation

Abstract: BackgroundSmall-diameter, myelinated axons are selectively susceptible to dysfunction in several inflammatory PNS and CNS diseases, resulting in pain and degeneration, but the mechanism is not known.MethodsWe used in vivo confocal microscopy to compare the effects of inflammation in experimental autoimmune neuritis (EAN), a model of Guillain-Barré syndrome (GBS), on mitochondrial function and transport in large- and small-diameter axons. We have compared mitochondrial function and transport in vivo in (i) heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
1
10
0
1
Order By: Relevance
“…The response to short-term HFD in young mice may represent a compensatory mechanism to counteract partial MMP loss and impaired energy production (Baqri et al, 2009), which may fail in old animals. In young mice, healthy polarized mitochondria are rapidly transported into areas of localized, experimentally induced saphenous nerve axon damage to avert local bioenergetics collapse (Sajic et al, 2018). The discrepancy between our in vitro and in vivo results perhaps reflects myelination state, which is absent in vitro but present around many saphenous axons in vivo (Ohno et al, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…The response to short-term HFD in young mice may represent a compensatory mechanism to counteract partial MMP loss and impaired energy production (Baqri et al, 2009), which may fail in old animals. In young mice, healthy polarized mitochondria are rapidly transported into areas of localized, experimentally induced saphenous nerve axon damage to avert local bioenergetics collapse (Sajic et al, 2018). The discrepancy between our in vitro and in vivo results perhaps reflects myelination state, which is absent in vitro but present around many saphenous axons in vivo (Ohno et al, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…Hence, a future study could focus on determining how protecting the lesion site affects the activation of apoptotic pathways in spinal cord segments distant from the injury site. Dysfunctional mitochondria are also linked to neuroinflammation [39], and hence, protecting mitochondria could have reduced the inflammation-mediated damage to the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, mitochondrial dysfunction occur in models of inflammatory peripheral neuropathy. Sajic et al (2018) found that in experimental autoimmune neuritis (a Guillain-Barre model), mitochondria in large and small diameter axons had depolarized, fragmented, and immobile mitochondria. The depolarized mitochondria in small diameter axons appeared to create a “plug” in the axon and even obstructed the traffick of other organelles ( Sajic et al, 2018 ).…”
Section: Hdac6 and Mitochondrial Dysfunction In Peripheral Neuropathymentioning
confidence: 99%
“… Sajic et al (2018) found that in experimental autoimmune neuritis (a Guillain-Barre model), mitochondria in large and small diameter axons had depolarized, fragmented, and immobile mitochondria. The depolarized mitochondria in small diameter axons appeared to create a “plug” in the axon and even obstructed the traffick of other organelles ( Sajic et al, 2018 ). Schwann cell mitochondria have also been found to be morphologically and functionally altered as well ( Muke et al, 2020 ).…”
Section: Hdac6 and Mitochondrial Dysfunction In Peripheral Neuropathymentioning
confidence: 99%